Mold detection and environmentally friendly prevention technology for animal specimens - Zhang Rui; Sunmei-Rong; Zeng Yayun; Chen Wei-Ling; Shang Zhuang Zhuang; Liu Yu; Wangkang; Cao Xiao-Min; Huang Xin-Yun; TANGJun-Yu; LIANGQI-Zhao (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Animal specimens are easily invaded and corroded by molds, which seriously affects the beautful shape and integrity of biological specimens, It's led to a huge economic loss. And the traditional methods & agentia of molds controlled are always spoisonous and polluted agentia. In this paper, review the detecting methods of animal specimens infected molds, exploring methods and reagents of prevention of molds,which can make the animal specimens be preserved for a long time without mold damage. This way would be green, environmental-friendly, and protect the human health and reduce economic losses.